2015
DOI: 10.1055/s-0035-1554672
|View full text |Cite
|
Sign up to set email alerts
|

The Elimination Rate after Clozapine Overdose in Chinese Schizophrenia Patients: A Population Pharmacokinetics Model Study

Abstract: PopPK can solve the problem of sparse data after overdose. The area under the concentration-time curve after clozapine overdose exhibited the "two peaks phenomenon." The reported toxic dosage could impact clozapine elimination after overdose. Delayed absorption of clozapine is the best explanation for this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…e number of concentration readings (observations) ranged from 22 to 1617, with a median of 410, and the median observation per patient was 3. e daily dose was reported in nine studies with a median of 291 mg/day (134-540 mg/day) [15-19, 21, 22, 25, 26]. Most of the included studies used NONMEM software for population pharmacokinetic model [18,[20][21][22][23][24][25][26].…”
Section: Analysis Methods Used In Pharmacokinetics Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…e number of concentration readings (observations) ranged from 22 to 1617, with a median of 410, and the median observation per patient was 3. e daily dose was reported in nine studies with a median of 291 mg/day (134-540 mg/day) [15-19, 21, 22, 25, 26]. Most of the included studies used NONMEM software for population pharmacokinetic model [18,[20][21][22][23][24][25][26].…”
Section: Analysis Methods Used In Pharmacokinetics Modelmentioning
confidence: 99%
“…After abstract and title scanning, 15 articles were retained for final evaluation. A total of 12 studies [15][16][17][18][19][20][21][22][23][24][25][26] published between 1987 and 2019 were included in this review, as demonstrated in Figure 1. Study characteristics of the included publications, samples, and concentrations are summarized in Table 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations